Compozit epoxy/Ppy-gamma-Fe2O3 bảo vệ chống ăn mòn kim loại - Lê Hiền, Nguyễn Thị; Trúc, Trịnh Anh; Oánh, Vũ Kế; Đức, Nguyễn Đăng (Vietnam Journal of Chemistry, 2014)
The three particles of γ-Fe2O3, Ppy and Ppy-oxit with very small sizes obtained by chemical synthesis are incorporated in epoxy to form protective composite films on Ct3 steel. The result of corrosion test show that these composite films can protect metal much better than epoxy films in the same thickness. The γ-Fe2O3oxide has a posibility of adherence improvement of the films. Ppy can self-heal by supply of its positive charge at corrosion metal possitions to maintain the metal in its passive state. So the presence of both γ-Fe2O3oxide and Ppy in epoxy films give the best protective result